2016
DOI: 10.1021/acs.jpclett.6b01787
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance of Nanoporous Carbon-Based Supercapacitors Is a Trade-Off between the Concentration and the Separability of the Ions

Abstract: Nanoporous carbon-based supercapacitors store electricity through adsorption of ions from the electrolyte at the surface of the electrodes. Room temperature ionic liquids, which show the largest ion concentrations among organic liquid electrolytes, should in principle yield larger capacitances. Here we show by using electrochemical measurements that the capacitance is not significantly affected when switching from a pure ionic liquid to a conventional organic electrolyte using the same ionic species. By perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 47 publications
8
91
3
Order By: Relevance
“…Such a quantitative agreement is in fact better than that previously obtained in similar simulations of CDC with ionic liquids and organic electrolytes (e.g., about 20% in Ref. [72]). In the latter cases, discrepancies are mainly due to the Ohmic drop in the experiments with no or little solvent.…”
Section: Resultssupporting
confidence: 43%
“…Such a quantitative agreement is in fact better than that previously obtained in similar simulations of CDC with ionic liquids and organic electrolytes (e.g., about 20% in Ref. [72]). In the latter cases, discrepancies are mainly due to the Ohmic drop in the experiments with no or little solvent.…”
Section: Resultssupporting
confidence: 43%
“…To improve the charging performance of carbon electrode materials, the ionic species must be continuously and swiftly transported to/from the carbon/electrolyte interface within the porosity with a minimum amount of free water . The latter factor contributes to the efficient ion packing by appropriate modification of the screening effect due to the presence of a solvent and improves in‐pore conductivity of ionic species …”
Section: Introductionmentioning
confidence: 99%
“…Following this study, the origin of the anomalous increase in capacitance has received considerable attention. It has been shown that the maximum volumetric capacitance was achieved when the carbon pore size matched that of the adsorbing electrolyte ions . The development of in situ experimental techniques, including the electrochemical quartz crystal microbalance (EQCM) and small‐angle X‐ray scattering (SAXS), has radically modified understanding of charge storage mechanisms and ion dynamics in nanoporous carbon‐based supercapacitors in aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%